2016
DOI: 10.3892/ol.2016.4517
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid sarcoma derived from the gastrointestinal tract: A case report and review of the literature

Abstract: Abstract. Myeloid sarcoma is a type of malignant neoplasm composed of myeloblasts that locates extramedullary. The present study reports the case of a 31-year-old female who presented with upper abdominal pain, melena, vomiting and jaundice. The abdominal computed tomography revealed a mass in gastric antrum area and possible infiltration of the duodenum, gallbladder and head of the pancreas, with possible retroperitoneal lymph node metastasis. The tumor grew quickly and led to serious obstructive jaundice. Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Hence, sometimes despite the best clinical judgement, only the specimen examination confirms the diagnosis. Our review showed 5 cases out of 17 to have isolated GB-MS without any bone marrow involvement (14,(25)(26)(27)(28). Bartley et reported an interesting case of disseminated extramedullary myeloid tumor of the gallbladder but without involvement of the bone marrow (28).…”
Section: Clinical Presentationmentioning
confidence: 77%
“…Hence, sometimes despite the best clinical judgement, only the specimen examination confirms the diagnosis. Our review showed 5 cases out of 17 to have isolated GB-MS without any bone marrow involvement (14,(25)(26)(27)(28). Bartley et reported an interesting case of disseminated extramedullary myeloid tumor of the gallbladder but without involvement of the bone marrow (28).…”
Section: Clinical Presentationmentioning
confidence: 77%
“…CT imaging can show various findings like single or multiple mass obstructing the lumen of the gut, or exophytic lesions involving the peritoneum [ 5 ]. Myeloid sarcoma has shown to involve various parts of the gastrointestinal tract like the oral cavity [ 6 ], esophagus, stomach, jejunum [ 7 ], gallbladder, bile ducts, pancreas [ 8 ], colon [ 9 ], liver [ 10 ], appendix [ 11 ], and anal region [ 12 ]. Our patient presented with watery diarrhea and it is uncommon for myeloid sarcoma to present with common gastrointestinal symptoms [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with systemic chemotherapy to achieve complete remission of MS followed by allogeneic hematopoietic stem cell transplantation is likely to achieve the best results as it is the case for AML [12][13][14]. Chevallier et al [13] assessed the outcome of 51 patients with MS who underwent allogeneic hematopoietic stem cell transplantation (alloHSCT) in a retrospective multicenter study.…”
Section: Discussionmentioning
confidence: 99%